Zakat Literacy and Altruism as Determinants of ASN Compliance in Paying Professional Zakat - Akib, Baso; Suharman, Dwi Tantri (IJBAMS: International Journal of Business Accounting Management Social Science, 2025)
This study aims to analyze the impact of zakat literacy and altruism on the level of ASN compliance in paying professional zakat. This study applies a quantitative approach using a descriptive design through a survey method. Initial data were obtained through questionnaire distribution and observation activities. The sampling method was carried out non-probabilistically using a purposive sampling approach, involving 44 participants as research respondents. Data analysis was carried out using multiple linear regression using IBM SPSS software version 25. The results of the study indicate that zakat literacy and altruism together have a positive and significant impact on ASN compliance, which means that both independent variables together contribute to increasing compliance in paying professional zakat